ADVANTAGES OF USING COMPUTER GRAPHICS IN THE FIELD OF DESIGN - Sobitovich, Mukhamedov Umarkhon (International Journal of Psychosocial Rehabilitation, 2020)
The use of computer graphics in the design area will be a great deal of convenience for the owners of this field. Graphics play a decisive role in design and advertising. This article discusses some of the uses of computer graphics in design.